DOI: 10.11606/t.61.2017.tde-12062017-161255
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol salivar e atenção auditiva sustentada

Abstract: Objetivo: Verificar uma possível correlação entre o nível de cortisol salivar e a atenção auditiva sustentada em crianças com fissura labiopalatina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…This result was also lower compared with studies with Brazilian children. [5][6][7][8][9]14,15 Lima et al 16 found values between 0.86 (SD ¼ 1.18) and 0.46 (SD ¼ 0.74), agreeing with the lowest values in the decrease in vigilance observed in the present study. This result demonstrates that adults have greater control over attention span and achieve a better sustained hearing attention maintenance compared with children.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This result was also lower compared with studies with Brazilian children. [5][6][7][8][9]14,15 Lima et al 16 found values between 0.86 (SD ¼ 1.18) and 0.46 (SD ¼ 0.74), agreeing with the lowest values in the decrease in vigilance observed in the present study. This result demonstrates that adults have greater control over attention span and achieve a better sustained hearing attention maintenance compared with children.…”
Section: Discussionsupporting
confidence: 88%
“…2,6 These results were lower when compared with studies with Brazilian children. [5][6][7][8][9]14,15 A study that applied the SAAAT in adults 16 found mean values of total error scores ranging from 1.00 (SD ¼ 1.30) to 3.26 (SD ¼ 5.86). These values were closer to those found in the present study compared with studies with children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations